High Sucrose Ingestion during a Critical Period of Vessel Development Promotes the Synthetic Phenotype of Vascular Smooth Muscle Cells and Modifies Vascular Contractility Leading to Hypertension in Adult Rats. (21st June 2022) - Castrejón-Téllez, Vicente; Rubio-Ruiz, María Esther; Cano-Martínez, Agustina; Pérez-Torres, Israel; Del Valle-Mondragón, Leonardo; Carreón-Torres, Elizabeth; Guarner-Lans, Verónica
Abstract : Cardiometabolic diseases, including hypertension, may result from exposure to high sugar diets during critical periods of development. Here, we studied the effect of sucrose ingestion during a critical period (CP) between postnatal days 12 and 28 of the rat on blood pressure, aortic histology, vascular smooth muscle phenotype, expression of metalloproteinases 2 and 9, and vascular contractility in adult rats and compared it with those of adult rats that received sucrose for 6 months and developed metabolic syndrome (MS). Blood pressure increased to a similar level in CP and MS rats. The diameter of lumen, media, and adventitia of aortas from CP rats was decreased. Muscle fibers were discontinuous. There was a decrease in the expression of alpha-actin in CP and MS rat aortas, suggesting a change to the secretory phenotype in vascular smooth muscle. Metalloproteinases 2 and 9 were decreased in CP and MS rats, suggesting that phenotype remains in an altered steady stationary state with little interchange of the vessel matrix. Aortic contraction to norepinephrine did not change, but aortic relaxation was diminished in CP and MS aortas. In conclusion, high sugar diets during the CP increase predisposition to hypertension in adults.